Pendidikan Islam Multikultural Pada Masa Rasulullah, Dan Sahabat - Iwan Kurniawan. ZP (Hikamatzu | Journal of Multidisciplinary, 2025)
This research aims to examine Multicultural Islamic Education during the Time of the Prophet Muhammad and His Companions. The method used in this research is a literature review. From the explanation above, it can be concluded that during the time of the Prophet Muhammad, Islamic education was a form of human culture that was acceptable and became a unified element in a pluralistic human culture, so that multicultural values ​​had an important position in its dissemination. Islamic education during the time of the Khulafaur Rosyidin had a position not much different from Islamic education during the time of the Prophet Muhammad, namely as a cultural value for Muslims.